Infrastructure Development in Edo State : Adapting to Constraints and Creating Capabilities - Porter, Douglas John; Rasool Cyan, Musharraf; Lee, Panthea; Brisson, Zack; Itegboje, Osione; Talsma, Adam (World Bank, Washington, DC, 2015)
Governor Adams Oshiomhole assumed office in November 2008 following a successful court appeal to retrieve the mandate given to him by the people of Edo. Widespread support from a variety of interest groups buttressed the legal challenge and helped create the political space for the Governor’s pursuit of an agenda focused on both reform and speedy delivery. Popular demand for reform was evident, but responding to this presented major challenges. Historically,Edo had been one of the best performing states in the country. Expectations were high that he would restore this status and address the perceived poor performance and allegations of corruption leveled against previous administrations. This case study is an attempt to better understand the process through which the Administration was able to maximize its delivery. This report is one product of several ongoing efforts by the World Bank to better understand how to better tailor its interventions to local realities with the overarching objective of improving its impact. To do this in the case of capital spending in Edo, it was necessary to craft a study method that suspended judgments about actual practices. Thus, rather than holding these practices up to international standards, and highlighting deficits and shortcomings in relation to those standards, the study purpose was to depict how the State administration had responded to the political priorities of the new Governor by adapting to the constraints it faced and creating new ways to deliver through infrastructure spending. This case study underlines the very rich and often messy reality that leaders frequently find when assuming office and the trade-offs that they are forced to make. In doing so, it reminds us of the political realities within which we work and, like other case studies recently undertaken to inform Bank engagements in Nigeria, finds that traditional blue print approaches in such circumstances are unlikely to work and that sequencing, tailoring to local contexts and adaptation along a non-linear road to reform is more feasible path.